Microevolution due to pollution in amphibians: A review on the genetic erosion hypothesis. (September 2015) - Fasola, E.; Ribeiro, R.; Lopes, I.
Abstract: The loss of genetic diversity, due to exposure to chemical contamination (genetic erosion), is a major threat to population viability. Genetic erosion is the loss of genetic variation: the loss of alleles determining the value of a specific trait or set of traits. Almost a third of the known amphibian species is considered to be endangered and a decrease of genetic variability can push them to the verge of extinction. This review indicates that loss of genetic variation due to chemical contamination has effects on: 1) fitness, 2) environmental plasticity, 3) co-tolerance mechanisms, 4) trade-off mechanisms, and 5) tolerance to pathogens in amphibian populations. Highlights: Effects of environmental stressors on the genetic diversity of natural populations of amphibians have usually been underestimated. Environmental pollution may reduce the genetic diversity of exposed amphibian populations. Genetic erosion can lead to reduced fitness and lack of adaptability to a changing environment. Abstract : Contaminant-driven genetic erosion is a major threat to population viability in amphibians.